PEMIMPIN NON-MUSLIM DALAM PERSPEKTIF IBNU TAIMIYAH - Khalik, Abu Tholib (Analisis: Jurnal Studi Keislaman, 2014)
THE APPOINTMENT A NON-MUSLIM LEADER IN PERSPECTIVE OF IBN TAYMIYYAH. Controversy on the appointment   of  a  non-Muslim  leader  among  the  majority  of Muslims emerges frequently. Historically, the issue has been going on for a long time and always invites debates among the Muslim scholars from time to time. In response to this issue, the scholars are divided  into  two  camps, most  of them  forbid it but others allow.  One  of the  scholars  allowing  the  appointment   was  Ibn Taymiyyah, a great Islamic thinker of his time. He was famous of his controversial statement “better led by a fair pagan than led by a tyrannical Muslim leader”. This article illustrates the relevance of “liberal” thought  of Ibn Taymiyyah  on the administration of state,  especially  on the  issue  of the  non-Muslim  leadership  in the middle of the vast majority  of Muslims. This view is quite relevant  to address the uncertainty  of the majority  of Muslims who are hostile to each other in choosing a candidate  while the proposed candidate does not deserve to be a leader.